Letter - Hitchman, E. A.
025a-0040-001 Ministry of Labour Montagu House Whitehall S.W.1 6th June 1940 Dear Sir, I am asked by Mr. Ernest Bevin to acknowledge the receipt of your two letters about Spanish seamen and the cost of living index figures. Mr. Bevin is looking into the two points and will write to you as soon as possible. Yours faithfully E.A.Hitchman Private Secretary. Sir Walter Citrine, K.B.E., Trades Union Congress, Transport House, Smith Square, S.W.1. 292/946/25a/40